Kinerja Campuran Stone Matrix Asphalt (SMA) Menggunakan Aspal Modifikasi Asbuton Murni Lawele - Qubro, Khodijah Al; Fauzi, Marguan; Nisumanti, Sartika; Febryandi, Febryandi; Hendarto, Sri (Universitas Batanghari Jambi, 2025)
Indonesia’s dependency on imported petroleum asphalt for road infrastructure development presents a sustainability challenge. Utilizing local resources such as Lawele natural asphalt (Asbuton) offers a strategic alternative to reduce this reliance. This study aims to evaluate the performance of Stone Matrix Asphalt (SMA) mixtures using pure Lawele-modified asphalt (PMA 2%) and compare it with mixtures made with unmodified Pen 60/70 asphalt and polymer-modified asphalt Starbit E-55. The research was conducted through a laboratory experimental approach using standard testing methods (AASHTO and SNI). The SMA mixtures were tested for Marshall Stability, draindown, Indirect Tensile Strength Ratio (ITSR), and Cantabro loss. Results showed that the Starbit E-55 mixture achieved the highest stability (707 kg), followed by PMA 2% (678 kg), and Pen 60/70 (638 kg). Both PMA 2% and Starbit E-55 mixtures exhibited 0% draindown, superior to the 0.022% of Pen 60/70. The PMA 2% mixture achieved an ITSR value of 82.55% and the lowest Cantabro loss at 1.97%, indicating excellent resistance to stripping and abrasion. In conclusion, the use of PMA 2% provides comparable or even superior structural and functional performance to synthetic polymer-modified asphalt and presents a more environmentally friendly binder alternative.